Distributed Distribution and Scheduling of Teaching Resources Based on a Random Matrix Educational Leadership Model - Ni, Bo; Xie, Xiaona (Informatica, 2024)
This paper proposes a distributed distribution and scheduling of teaching resources based on the random matrix educational leadership model. The system adopts a distributed structure based on scheduling servers, and each distribution centre can independently provide personalized distribution services to resource users under the domination of the scheduling server. This paper proposes a professional system-based teaching resource model SLRM based on the SCORM model to establish a common architecture framework and a hierarchical description of teaching resources. Secondly, to reuse teaching resources at multiple levels and realize the sharing of teaching resources, this paper analyzes the LOM learning object metadata standard, Dublin Core metadata standard, IMS learning resource metadata specification, and IMS learning resource metadata specification. Based on the analysis of the LOM learning object metadata standard, Dublin Core metadata standard, IMS learning resource metadata specification, and education resource construction technical specification CELTS-41, this paper proposes the metadata representation method of network teaching resources based on a professional system. The system adopts ant colony clustering and other supporting technologies as personalized services. In addition, the task scheduling optimization based on the ant colony algorithm is adopted in the scheduling server, which effectively solves the distribution problem between resource user groups and distributed distribution centres, thus realizing the system load balancing. Finally, simulation and comparison experiments confirm the effectiveness of the distributed distribution system of educational resources. The practical application of the system will form a new and effective resource distribution service system, so this system has excellent use-value and promotion significance.